2019
DOI: 10.2196/14382
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Impact of Public-Academic Partnerships in Fostering Policymakers’ Use of Research Evidence: Proposal to Test a Conceptual Framework

Abstract: Background Previous research has reported that public-academic partnerships (PAPs) can effectively promote PAP leaders’ use of research evidence in improving youth outcomes. However, the existing literature has not yet clarified whether and how PAP leaders’ use of research evidence evolves along the PAP life cycle and whether PAP partners’ concordant perceptions of usefulness of their PAP has an impact on PAP leaders’ use of research evidence. Developing a conceptual framework that recognizes the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Although previous studies have demonstrated the positive impact of PAPs on youth mental health and well-being outcomes, few empirical studies have examined whether and how PAP contexts and mechanisms evolve through the PAP life cycle and which PAP contexts and mechanisms foster public agency leaders’ use of research evidence to improve youth mental health and well-being [ 11 ]. Public mental health and child welfare agencies are expected to increase the use of evidence-based care to improve mental health and well-being of vulnerable youth [ 12 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous studies have demonstrated the positive impact of PAPs on youth mental health and well-being outcomes, few empirical studies have examined whether and how PAP contexts and mechanisms evolve through the PAP life cycle and which PAP contexts and mechanisms foster public agency leaders’ use of research evidence to improve youth mental health and well-being [ 11 ]. Public mental health and child welfare agencies are expected to increase the use of evidence-based care to improve mental health and well-being of vulnerable youth [ 12 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research on individual components of the partnership process has revealed important information about factors that support successful partnerships, the literature has yet to bring these components together into an integrated framework [ 11 ]. Such a framework would offer a way to examine the totality of PAPs, including the contexts in which they initiate and mature, the mechanisms that propel them forward, and the outcomes that they define and achieve at various stages in relation to public care agency leaders’ use of research evidence.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations